PERISTILAHAN DALAM BEUMO (BERLADANG PADI) PADA MASYARAKAT DAYAK KETUNGAU SESAT: KAJIAN SEMANTIK - Simon, Pabianus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study focused on observations of the activities beumo (shifting cultivation) on the Dayak Ketungau Sesat community. Beumo (shifting cultivation) in question is still traditional, either a tool or process. The researchers focused on the study of the semantics of the research problem in the form of description, components of meaning and cultural meaning terminology beumo (shifting cultivation). This study aimed to describe the term, components of meaning and cultural meaning contained in beumo (shifting cultivation) terminology Dayak Ketungau Sesat community. Based on the research conducted, the researchers managed to collect 124 terms as research data. Overall the data consists of seven classification terms, namely 31 terms in the form of a classification tool, 41 terms in the form of the classification process, 14 terms in the form of the classification name of the place, 10 terms in the form of classification of rice growth, 14 terms in the form of classification of soil type, 9 terms in the form of classification results, and 5 terms in the form of classification marks. Keywords: Terminology, shifting cultivation, Dayak Ketungau Sesat